PERILAKU KONSUMEN DALAM MEMBELI TANAMAN HIAS DI KOTA PEKANBARU - Mai Hendra Sipayung; Rosnita Rosnita; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2017)
Consumer behavior on a product can be influenced by several factors one of them is psychological factors, social factors, and situational factors, so that consumers will take the decision to make purchases of ornamental plants. The purpose of the study there are two: 1) Characteristics of buyers of ornamental plants in Kota Pekanbaru. 2) Analyzing consumer behavior factor in buying ornamental plants in Kota Pekanbaru. This research uses survey method in Pekanbaru city which started from August 2016 until March 2017. Consumer respondent of ornamental plants 50 people taken by purposive sampling with consideration of kiosk business has more than 2 years. Analyze the data using Likert scale and presented descriptively. The results showed that: Consumer behavior is determined by psychological, social, and situational factors. Of the three factors, social factors are still less instrumental in determining consumers to buy ornamental plants in Pekanbaru City.